1985
DOI: 10.1002/1097-0142(19850801)56:3<480::aid-cncr2820560312>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific active immunotherapy in patients with adenocarcinoma of the colon utilizing tumor-associated antigens (TAA). A phase I clinical trial

Abstract: Twenty-two patients received specific active immunotherapy (TAA vaccine once per month for 3 months), with the duration of follow-up, as of July 1984, ranging from 3 months to 36 months (median, 21 months). Of these, seven had Dukes B2, seven had Dukes C, and eight had Dukes D lesions. All received surgical resection, and those with Dukes D disease underwent resection of all metastases where possible, with six clinically disease-free at the time of initiation of therapy. The age range of the 22 patients was 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…The idea behind immunotherapy of cancer is that transformed cells express antigens that, in principle, can be recognized by the immune system and can be targeted for specific elimination of tumor cells [54,55]. Potential tumor antigens are, for example, mutated oncogenes or tumor-suppressor genes that were causative for the tumor (for example the EVT6-AML1 fusion protein in lymphoblastic leukemia [56]) or proteins that are normally rarely expressed in differentiated cells but are expressed in the malignant tissue like expression of the melanoma antigen-encoding genes (MAGE) in melanoma cells [57] or carcinoembryonic antigen (CEA) [58].…”
Section: Immunotherapymentioning
confidence: 82%
“…The idea behind immunotherapy of cancer is that transformed cells express antigens that, in principle, can be recognized by the immune system and can be targeted for specific elimination of tumor cells [54,55]. Potential tumor antigens are, for example, mutated oncogenes or tumor-suppressor genes that were causative for the tumor (for example the EVT6-AML1 fusion protein in lymphoblastic leukemia [56]) or proteins that are normally rarely expressed in differentiated cells but are expressed in the malignant tissue like expression of the melanoma antigen-encoding genes (MAGE) in melanoma cells [57] or carcinoembryonic antigen (CEA) [58].…”
Section: Immunotherapymentioning
confidence: 82%
“…Rather, the immune system for the most part only detects the presence of a relatively small level of tumor antigen, and exerts a minimal response through a process termed "tumor surveillance". In the original Hollinshead et al [4] vaccine trials, it was shown that an ideal response to tumor antigen occurred with the administration of a threshold level of approximately 750-1000 µg of antigen administered intradermally along with an adjuvant. In most malignancies the level of immunogen (TAA) expression rarely exceeds 30-50 µg.…”
Section: Discussionmentioning
confidence: 99%
“…They were first identified by Hollinshead et al [4] from pooled allogeneic tumor specimens obtained following surgery. Further purification by sephadex column chromatography and isoelectric focusing led to the identification of these tumor associated antigens.…”
Section: Introductionmentioning
confidence: 99%
“…A biologic approach is currently being pursued to identify immunogenic functional neoantigens. Ensituximab is one of several monoclonal antibodies raised against an allogeneic colorectal cancer vaccine that had previously been tested in human clinical trials in the USA [14]. Surgical samples from dozens of patients with various stages of colorectal cancer including metastatic foci were obtained as a source for antigen screening.…”
mentioning
confidence: 99%
“…Surface membrane from pooled allogeneic tumor was fractionated and various molecular weight components were tested for immunogenic reactivity which was the basis of the initial vaccine. Results revealed safety of the vaccine, but clinical benefit that directly correlated with the ability of the patients' immune system to mount IgG responses against the vaccine [14]. Based on the results of these early studies, the original vaccine was used as the source of antigenic material to produce monoclonal antibodies that specifically reacted with colorectal cancer and could kill tumor via antibody-dependent, cell-mediated cytotoxicity.…”
mentioning
confidence: 99%